How Does the Future Economics Teacher Against Digital Economics? The Perspective of Economics Behaviour and Role of Social Support - Hanif Ramadhan Fahmi Putra; Muhammad Ari Kusuma; Faizal Ansyori; Indra Febrianto; Umi Hidayati (Economics Education Department Universitas Negeri Semarang, 2024)
The study aims to find a structural fit model related to students’ readiness to face the digital economy in the perspective of irrational behavioral economic theory. The study uses quantitative Explanatory research with a population of undergraduate students of Economics Education at the East Java PGRI College and uses a proportional random sampling with total of 351 students. Data were collected by questionnaires using linkert scale and were analysed by SEM-PLS data analysis . The findings show that digital economic skills don’t significantly mediate the relationship between herd behavior, loss aversion, and student readiness. However, the digital economy succeeded in mediating the influence of confirmation bias on student readiness because of helped reduce the impact of confirmation bias on student readiness by offering access to diverse information and developing critical thinking skills. This study contributes are become theoretical literature on the functional relationship between irrational behavior, digital economic skills, social support and student readiness studied in the context of behavioral economics. It can be a reference for developing educational models in digital era learning and reference for further researchers to develop appropriate policy recommendations by involving several related stakeholders.